2016
DOI: 10.1515/raon-2016-0033
|View full text |Cite
|
Sign up to set email alerts
|

The proliferation marker Ki67, but not neuroendocrine expression, is an independent factor in the prediction of prognosis of primary prostate cancer patients

Abstract: BackgroundNeuroendocrine markers, which could indicate for aggressive variants of prostate cancer and Ki67 (a well-known marker in oncology for defining tumor proliferation), have already been associated with clinical outcome in prostate cancer. The aim of this study was to investigate the prognostic value of those markers in primary prostate cancer patients.Patients and methodsNSE (neuron specific enolase), ChrA (chromogranin A), Syp (Synaptophysin) and Ki67 staining were performed by immunohistochemistry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…It is well known that Ki67 is a biomarker of cellular proliferation in tumors, and is associated with poor prognosis [34, 35]. In T lymphocytes, Ki67 expression is also a good indicator of T cell activation and reinvigoration [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that Ki67 is a biomarker of cellular proliferation in tumors, and is associated with poor prognosis [34, 35]. In T lymphocytes, Ki67 expression is also a good indicator of T cell activation and reinvigoration [16].…”
Section: Discussionmentioning
confidence: 99%
“…The marker of proliferation, Ki-67 (MKI67), functions to mark tumor cell proliferation, including in the prostate, and has a close relation to the epithelial-mesenchymal transition (EMT) (Lindsay et al, 2016). Ki67 may improve the prediction of prostate cancer outcomes based on pathological standard parameters, improving prognosis as well as the monitoring of prostate cancer patients (Pascale et al, 2016). TOP2A is considered to be a biomarker for early identification of patients who have increased metastatic potential (Labbé et al, 2017).…”
Section: Selection Real Core Genesmentioning
confidence: 99%
“…Moreover, our results also showed a positive correlation between plasma C-MYC level and Ki67 index. It has been reported that the protein Ki67 is expressed in the nucleus of cycling cells and used to measure the activity of cell proliferation [47][48][49]. Ki67 index is recognized as an independent prognostic factor in breast cancer [50][51][52][53][54], high Ki67 index is associated with a poor prognosis in breast cancer.…”
Section: Discussionmentioning
confidence: 99%